An exploration of the hypothesis that testosterone is implicated in the psychological functioning of women with polycystic ovary syndrome (PCOS). (January 2018) - Barry, J.A.; Qu, F.; Hardiman, P.J.
Abstract: One of the diagnostic features of polycystic ovary syndrome (PCOS) is elevation of the androgen, testosterone. It is known that women with PCOS are more likely to suffer from psychological problems, especially anxiety and depression, than other women. However, little is known of how much of this is due to testosterone, and if so, what the mechanism(s) might be. This study explores the hypothesis that testosterone impacts women with PCOS both directly and indirectly, via testosterone currently in the bloodstream and through prenatal exposure. It is hypothesised that direct effects occur when testosterone acts directly upon receptors; indirect effects occur where the impact of testosterone is mediated via another variable; activational effects are ephemeral and are caused by testosterone in the bloodstream; organizational effects occur prenatally and cause permanent changes. Four pathways are hypothesised in this paper: 1/ a direct and activational pathway which improves mental rotation ability; 2/ an indirect and activational pathway, whereby distress is caused when the physiological symptoms of testosterone are experienced as embarrassing or otherwise disturbing; 3/ an indirect and organizational effect on mood, where elevated prenatal testosterone predisposes women with PCOS to low blood sugar levels and thus low mood; 4/ and finally, it is suggested that the pathway from biology to psychology can be travelled in reverse, with a direct activational effect of relaxation training on the reduction of adrenal androgens. Testing these hypotheses has important implications for our understanding of PCOS, and our ability to treat this condition more effectively.